Predictability of European winter 2015/2016. (19th January 2017) - Scaife, Adam A.; Comer, Ruth; Dunstone, Nick; Fereday, David; Folland, Chris; Good, Elizabeth; Gordon, Margaret; Hermanson, Leon; Ineson, Sarah; Karpechko, Alexey; Knight, Jeff; MacLachlan, Craig; et al.
Abstract: We present a case study of long range forecasts for Northern Hemisphere winter 2015/2016. This winter produced the strongest El Niño event since 1997/1998 and equatorial Pacific sea surface temperature anomalies exceeded 3 °C. Other factors relevant to the Northern Hemisphere extratropical atmosphere circulation included a strong westerly phase of the Quasi‐Biennial Oscillation (QBO) and very strong winds in the stratospheric polar night jet in early winter. At the surface, intense cyclonic extratropical circulation anomalies occurred in early winter in both the North Pacific and North Atlantic, consistent with known teleconnections to these phases of El Niño–Southern Oscillation, the QBO and the polar night jet. The midlatitude flow was very westerly in early winter and less westerly and sometimes northerly in late winter, when sudden stratospheric warming events also occurred. We show that initialised climate predictions were able to capture the winter mean flow pattern at seasonal lead times from well before the start of winter. In this special case, not only the winter mean flow pattern, but also some aspects of the sub‐seasonal evolution were skilfully predicted. We show that the winter of 1982/1983 was closely analogous to winter 2015/2016 in both the predictable driving factors and the forecast winter circulation. This case study adds to the evidence that the north Atlantic circulation can be predictable on seasonal timescales and advance warning of the increased risk of intense rainfall and storminess which caused extreme flooding in the UK in December was possible in this case.